2002
DOI: 10.1002/cm.10036
|View full text |Cite
|
Sign up to set email alerts
|

Separating centrosomes interact in the absence of associated chromosomes during mitosis in cultured vertebrate cells

Abstract: We detail here how "free" centrosomes, lacking associated chromosomes, behave during mitosis in PtK(2) homokaryons stably expressing GFP-alpha-tubulin. As free centrosomes separate during prometaphase, their associated astral microtubules (Mts) interact to form a spindle-shaped array that is enriched for cytoplasmic dynein and Eg5. Over the next 30 min, these arrays become progressively depleted of Mts until the two centrosomes are linked by a single bundle, containing 10-20 Mts, that persists for > 60 min. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 72 publications
5
23
0
Order By: Relevance
“…A defect in the centrosome-independent spindle assembly pathway may go unnoticed because of the ability of the centrosomes to form bipolar spindles, even in the absence of chromosomes (e.g. Brunet et al, 1998;Bucciarelli et al, 2003;Faruki et al, 2002;Walczak et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A defect in the centrosome-independent spindle assembly pathway may go unnoticed because of the ability of the centrosomes to form bipolar spindles, even in the absence of chromosomes (e.g. Brunet et al, 1998;Bucciarelli et al, 2003;Faruki et al, 2002;Walczak et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that antimitotic agents, including the Eg5-inhibitor monastrol, take 10-15 minutes to achieve inhibitory concentrations inside cells. [10] Thus, greater temporal control in perturbing this process is critical. Light can be controlled with outstanding temporal and spatial precision to localize photochemistry noninvasively in a biological context.…”
mentioning
confidence: 99%
“…In C. elegans embyros, Ran is required for spindle assembly, but RCC1 is not (Askjaer et al, 2002). It is likely that centrosomes dominate spindle assembly when they are present and can override any defects in a Ran-dependent stabilization pathway (e.g., Faruki et al, 2002).…”
Section: Chromosomes As Chemical Depots Of Microtubule Regulatory Facmentioning
confidence: 99%
“…While sufficient to initiate the association between two half spindles, polar microtubule cross-linkages may not be sufficient to maintain a spindle structure. For instance, separated asters devoid of chromosomes initially form a Regulated Assembly of the Mitotic Spindle 105 bipolar spindle-like array, but this structure decays over time (Faruki et al, 2002). Thus, chromosomes remain an important contender in both spindle assembly and maintenance.…”
Section: Chromosomes As Mechanical Bridges and Force Producing Organementioning
confidence: 99%